Resveratrol sequentially induces replication and oxidative stresses to drive p53-CXCR2 mediated cellular senescence in cancer cells - Boxuan Li; Dong Hou; Haiyang Guo; Haibin Zhou; Shouji Zhang; Xiuhua Xu; Qiao Liu; Xiyu Zhang; Yongxin Zou; Yaoqin Gong; Changshun Shao (2017)
Abstract Resveratrol (RSV) acts either as an antioxidant or a pro-oxidant depending on contexts. RSV-treated cancer cells may experience replication stress that can lead to cellular senescence or apoptosis. While both oxidative and replication stresses may mediate the anti-proliferation effect of RSV, to what extent each contributes to the impaired proliferation in response to RSV remains uncharacterized. We here report the study of the roles of replication and oxidative stresses in mediating cellular senescence in cancer cells treated with RSV. RSV induced S-phase arrest and cellular senescence in a dose-dependent manner in U2OS and A549 cancer cells as well as in normal human fibroblasts. We observed that nucleosides significantly alleviated RSV-induced replication stress and DNA damage response, and consequently attenuating cellular senescence. While the elevation of reactive oxygen species (ROS) also mediated the pro-senescent effect of RSV, it occurred after S-phase arrest. However, the induction of ROS by RSV was independent of S-phase arrest and actually reinforced the latter. We also demonstrated a critical role of the p53-CXCR2 axis in mediating RSV-induced senescence. Interestingly, CXCR2 also functioned as a barrier to apoptosis. Together, our results provided more insights into the biology of RSV-induced stress and its cellular consequences.